2006
DOI: 10.1136/bmj.332.7554.1343
|View full text |Cite
|
Sign up to set email alerts
|

What health services could do about climate change

Abstract: They must embrace sustainable development and reduce their ecological footprints

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(18 citation statements)
references
References 2 publications
0
18
0
Order By: Relevance
“…At the same time, healthcare and medical institutions conduct different kinds of therapeutic activities that result in the production of infectious waste, sharp objects, radioactive waste, and chemical materials. 1 Research conducted by Yoan Kagoma, a medical director, showed that proper waste segregation is the single most effective cost-saving measure; therefore, he has suggested that all hospitals should compulsorily put this into practice. 2 In addition, a hospital should reduce its ecological footprint by practicing comprehensive medical waste segregation and integrating "reduce, reuse, recycle" concepts into its medical waste management system.…”
Section: Effective Hospital Waste Classification To Overcome Occupatimentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, healthcare and medical institutions conduct different kinds of therapeutic activities that result in the production of infectious waste, sharp objects, radioactive waste, and chemical materials. 1 Research conducted by Yoan Kagoma, a medical director, showed that proper waste segregation is the single most effective cost-saving measure; therefore, he has suggested that all hospitals should compulsorily put this into practice. 2 In addition, a hospital should reduce its ecological footprint by practicing comprehensive medical waste segregation and integrating "reduce, reuse, recycle" concepts into its medical waste management system.…”
Section: Effective Hospital Waste Classification To Overcome Occupatimentioning
confidence: 99%
“…1,2 Empiric antimicrobial therapy has led to the increased use of carbapenems for initial broad-spectrum treatment of nosocomial infections worldwide. 1,2 A few studies have suggested that carbapenems have a differential impact on gut ecology, defined as the emergence of carbapenem-resistant Acenitobacter baumannii (CRAB) and carbapenem-resistant Pseudomonas aeruginosa (CRPA).…”
Section: Effective Hospital Waste Classification To Overcome Occupatimentioning
confidence: 99%
“…Moreover, the industry employs 1 out of 8 Americans, directly or indirectly, and drives upwards of 15% of the gross domestic product (58). Owing to the sheer size of health care institutions, the decisions that health care purchasers make have a dramatic impact on the marketplace (17).…”
Section: Hospital Preparationmentioning
confidence: 99%
“…Medical and healthcare institutional can be the source of the lifesaving medical interventions but it also plays a significant role as a vital energy hogs. At the same time, healthcare and medical institutional, conduct different kinds of therapeutic activities, which result in the production of infectious waste, sharp objects, radioactive wastes and chemical materials (Coote, 2006). In order to this, the medical waste management has become a blooming issues among public all over the countries after few medical institutional reported on ecological footprint that 384 times greater than the plot of land on which medical institutional located.…”
Section: Introductionmentioning
confidence: 99%